KEWAJIBAN MENJAGA KERAHASIAAN PENERIMA LISENSI RAHASIA DAGANG - Endang Retnowati (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2004)
Trade Secret or Confidential Information has been regulated in UU No. 30, 2000, has given protection or intellectual property rights in trade and science in Indonesia, both for the license’s owner and the received party.